IMPLEMENTATION OF SCAFFOLDING STRATEGY TO IMPROVE CHEMICAL LITERATION CAPABILITIES AND SELF-EFFICACY THROUGH USE OF THE PROBLEM-BASED LEARNING MODEL AT COLLOID MATERIAL - Harsono Hammasa; Iriani Bakti; Muhammad Kusasi (Universitas Lambung Mangkurat, 2024)
The scaffolding strategy is designed to address difficulties in understanding materials. By using scaffolding, it is possible to improve chemical literacy and self-efficacy. The teaching of colloidal material has not represented abstract material adequately. Therefore, to enhance chemical literacy and self-efficacy, a student-centered learning model is needed, namely the problem-based learning (PBL) model. This study aims to determine the differences in chemical literacy and self-efficacy in the scaffolding strategy with the PBL model, the relationship between chemical literacy and self-efficacy, and student responses to the scaffolding strategy with the PBL model.The research method used was quasi-experimental with a pretest-posttest non-equivalent control group design. Purposive sampling was employed for sample selection. The study used descriptive and inferential analysis, comparing dependent variables in the experimental class using the scaffolding strategy with the PBL model and the control class using the PBL model, with a sample of 73 students.The results indicate a significant difference in chemical literacy and self-efficacy between the scaffolding strategy with the PBL model and a positive response from students in terms of chemical literacy and self-efficacy after treatment. The Pearson correlation (rxy) between chemical literacy and self-efficacy was 0.674, indicating a strong correlation. The R2 value was 0.454, meaning that self-efficacy contributes 45.4% to chemical literacy. Students showed a positive response to the scaffolding strategy with the PBL model compared to without the scaffolding strategy. Therefore, the implementation of the scaffolding strategy with the PBL model can enhance chemical literacy and self-efficacy by providing students with assistance in understanding materials and problem-solving. The application of the scaffolding model in PBL activities should be modified using supportive media with characteristics similar to those in this study.